Genomes reveal genetic diversity of Piscine orthoreovirus in farmed and free-ranging salmonids from Canada and USA. Issue 2 (31st July 2020) - Siah, A; Breyta, R B; Warheit, K I; Gagne, N; Purcell, M K; Morrison, D; Powell, J F F; Johnson, S C
Abstract: Piscine orthoreovirus (PRV-1) is a segmented RNA virus, which is commonly found in salmonids in the Atlantic and Pacific Oceans. PRV-1 causes the heart and skeletal muscle inflammation disease in Atlantic salmon and is associated with several other disease conditions. Previous phylogenetic studies of genome segment 1 (S1) identified four main genogroups of PRV-1 (S1 genogroups I–IV). The goal of the present study was to use Bayesian phylogenetic inference to expand our understanding of the spatial, temporal, and host patterns of PRV-1 from the waters of the northeast Pacific. To that end, we determined the coding genome sequences of fourteen PRV-1 samples that were selected to improve our knowledge of genetic diversity across a broader temporal, geographic, and host range, including the first reported genome sequences from the northwest Atlantic (Eastern Canada). Nucleotide and amino acid sequences of the concatenated genomes and their individual segments revealed that established sequences from the northeast Pacific were monophyletic in all analyses. Bayesian inference phylogenetic trees of S1 sequences using BEAST and MrBayes also found that sequences from the northeast Pacific grouped separately from sequences from other areas. One PRV-1 sample (WCAN_BC17_AS_2017) from an escaped Atlantic salmon, collected in British Columbia but derived from Icelandic broodstock, grouped with other S1 sequences from Iceland. Our concatenated genome and S1 analysis demonstrated that PRV-1 from the northeast Pacific is genetically distinct but descended from PRV-1 from the North Atlantic. However, the analyses were inconclusive as to the timing and exact source of introduction into the northeast Pacific, either from eastern North America or from European waters of the North Atlantic. There was no evidence that PRV-1 was evolving differently between free-ranging Pacific Salmon and farmed Atlantic Salmon. The northeast Pacific PRV-1 sequences fall within genogroup II based on the classification of Garseth, Ekrem, and Biering (Garseth, A. H., Ekrem, T., and Biering, E. (2013) 'Phylogenetic Evidence of Long Distance Dispersal and Transmission of Piscine Reovirus (PRV) between Farmed and Wild Atlantic Salmon', PLoS One, 8: e82202.), which also includes North Atlantic sequences from Eastern Canada, Iceland, and Norway. The additional full-genome sequences herein strengthen our understanding of phylogeographical patterns related to the northeast Pacific, but a more balanced representation of full PRV-1 genomes from across its range, as well additional sequencing of archived samples, is still needed to better understand global relationships including potential transmission links among regions.